(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
• V.P. Kashchenko’s socio-pedagogical experience is an innovation for his time. The system he suggested helped to make the socialization process of the children in risk groups effective. The creation of a sanatorium-school based on the principles of humanistic pedagogy has enabled the children of risk groups to be socialized in a healthy moral and psychological atmosphere, while taking into account the specifics of their problem, to be treated, educated and brought up at the same time. The sanatorium-school was formed on the basis of the "family" model: three families, which are independent in their activities, each with its own therapeutic, educational programs, but collective work activities such as garden work, hand craft or participation in the choir unites them. Applying various innovative technologies and methods such as art therapy: music therapy, dancing, handcraft and applying customized learning programs for each family the team of professionals at the sanatorium-school managed to achieve V. Kashchenko’s adopted motto: limited capacity is not a sentence.